Psoriatic – Arthritis among Psoriasis Patients Attending Skin Clinics n Dar es Salaam, Tanzania (Tanzania Medical Journal, 2007)
Background: Psoriasis is an autoimmune inflammatory disease which primarily affects the skin but joints may also be targeted. Psoriatic arthritis is a destructive inflammatory arthropathy and ensethopathy which is considered to be rare in sub Saharan Africa. Left untreated the condition is permanently disabling. There are no studies in Dar es Salaam that have described psoriatic arthritis among psoriasis patients seen at dermatology clinics.Broad objective: To describe psoriatic arthritis among psoriasis patients attending specialized skin clinics in Dar es Salaam.Study design: Hospital – based – cross – sectional descriptive studyStudy setting: Muhimbili National Hospital and three private hospitals in the City of Dar es SalaamStudy population: All patients attending skin clinics at Muhimbili National Hospital and three private hospitals in Dar es SalaamMeasures of outcome: Psoriasis and psoriatic arthritisIntervention: Patients attending skin clinics at Muhimbili National Hospital and three private hospitals in Dar es Salaam were examined for the presence of psoriasis. Psoriasis was diagnosed clinically in most cases. Psoriatic arthritis was diagnosed according to the Moll and Wright criteria.Results: A total of 42 patients with psoriasis were recruited into the study. Males constituted 71%. The mean age at onset of psoriasis was 37 years and the psoriasis onset age – group with the highest number of patients (33%) was 31 – 40 years. Joint complaints of different types were encountered in 21% (9/42) and of these only 2 patients (5%) had psoriatic arthritis. Of the 2 patients with psoriatic arthritis, one was a known HIV sero positive. Conclusion and recommendations: Psoriatic arthritis occurs at a lower frequency among psoriasis patients in Dar es Salaam but the actual prevalence remains undetermined. More comprehensive studies are required to establish its magnitude.Tanzania Medical Journal Vol. 22 (1) 2007: pp. 40-42